Anemia dan Retensio Plasenta dengan Kejadian Perdarahan Post Partum - Zuitasari, Andini (JOURNAL OF HEALTH SCIENCE, 2025)
Retention of the placenta is the retention or not delivery of the placenta until or more than 30 minutes after the baby is born. Most of the disruption of placental detachment is caused by impaired uterine contractions. Bleeding is responsible for 28% of maternal deaths, one of the causes of maternal death in most cases of bleeding in the puerperal mass that occurs due to retained placenta, so it is necessary to do good and correct handling efforts that can be realized by efforts to improve the skills of health workers, especially in childbirth assistance. Objective: to determine the relationship between anemia and retained placenta with the incidence of postpartum hemorrhage. This study used a quantitative analytical survey research design using a cross sectional approach where the independent and dependent variables were. The sample of this study used a random sampling technique method. The sample of this study amounted to 156 respondents. Data analysis was carried out in two stages, namely univariate analysis and bivariate analysis with Chi-square statistical test. The results of the bivariate analysis found that there was a relationship between anemia (p value = 0.001) and the incidence of postpartum. The suggestions are expected to be taken into consideration in decision making, can improve the quality of service and especially regarding the incidence of postpartum hemorrhage. Keywords: Anemia, Placental Retention, and Post Partum Bleeding